Drug resistance mechanism and reversal strategy in lung cancer immunotherapy - Xu, Yishi; Liu, Yaqing; Ge, Yi; Li, Haozhe; Zhang, Yi; Wang, Liping (Frontiers in Pharmacology, 2023)
Among all malignant tumors, lung cancer has the highest mortality and morbidity rates. The non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) are the most common histological subtypes. Although there are a number of internationally recognized lung cancer therapy regimens, their therapeutic effects remain inadequate. The outlook for individuals with lung carcinoma has ameliorated partly thanks to the intensive study of the tumor microenvironment and immune checkpoint inhibitors. Numerous cancers have been effectively treated with immunotherapy, which has had positive therapeutic results. Global clinical trials have validated that PD-1/PD-L1 inhibitors are effective and safe for treating lung cancer either independently or in combination, and they are gradually being recommended as systemic treatment medications by numerous guidelines. However, the immunotherapy resistance restricts the immunotherapy efficacy due to the formation of tumor immunosuppressive microenvironment and tumor mutations, and immunotherapy is only effective for a small percentage of lung cancer patients. To summarize, while tumor immunotherapy is benefiting an increasing number of lung cancer patients, most of them still develop natural or acquired resistance during immunotherapy. Consequently, a crucial and urgent topic is understanding and tackling drug resistance triggered by immunotherapy in lung cancer treatment. This review will outline the presently recognized mechanisms of immunotherapy resistance and reversal strategies in lung cancer.